Current ways of expressing voice in Ukrainian language - Yanush , Oleg (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article covers consideration and analysis of syntactic rules for the category of voice in modern Ukrainian language, particularly in the sphere of professional communication. The proposed study traces the definitions of active and passive voice constructions, introduces definitions of direct and indirect subject, and also analyzes the formation of the indirect subject, indicating its belonging to the class of animate and inanimate objects. The article considers various ways of correct conveying of thoughts, accurate and logical presentation of the context, which can be achieved through particular syntactic norms of different styles in professional speech, using such verb voices as active and passive, as well as the reflexive voice, which is inherent, in particular, to Ukrainian language. Therefore, the author analyzes semantic structure of a clause from the point of view on reflecting transient process. Indicating the direct order of words in the sentence, it is manifested that subject in a sentence expresses a person or an object, a phenomenon that performs certain action, an object or a person that is in specific texts like natural, technical or social narratives, where subjects may be animate and inanimate ones. Formulating the idea through linguistic means in such clauses, statements, etc., it is affirmed that the semantic structure of the sentence is to be structured by definite syntactical model. Also, through the study it has been defined the status of verbs with the postfix -sia (ukr. -ся) in contemporary Ukrainian language. Its uncertainty of usage is sometimes observed mentioning passive and reflexive voices in Ukrainian. This postfix historical development of applying within the morphological structure of the word, word combination and clause has been analyzed. The author believes that it indicates the action is accomplished by the subject itself. The characteristic features of the development of reflexive verbs used for various semantic connotations are distinguished considering relationship between subject and object in action, which allowed the author to distinguish at least their six qualifications keeping in mind much broader verb classification within reflexive constructions. Taking into consideration that the mentioned verbs with postfix -sia are referred to the reflexive voice. It is emphasized that verbs with the mentioned postfix are derived from transitive verbs. In conclusion it is emphasized that in modern Ukrainian literary language, and especially professional one, two-part active and passive constructions are commonly used, and the usage of reflexive voice needs further scientific investigation and study.